(3TQM GdcGajI (B((3GdUZjQ(B)s - (3Qcf GdOjf GdMSf Hf eMeO (B((3QVi GdOjf(B) (3Hf TQa TGg GdMSjfj GdCSJQGHGPjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3MSf Hf Ydj Hf CMeO Hf GdJfhNj s)
(3ChdgG (B:s
(3dG jRjO Ydi SJI(B: (3GSe hGSe, hGSe haYd, hGSe hMQa, haYd haYd, haYd hMQa, hMQa hMQa s
(3BNQgG (B:s
(3dCf GdJfhjf dGRe, hfhf GdJCcjO LGFRI GYJHGQ GdLGFR YfO YQhV GdMPa s
(3GdfSNI HgG MhGTs
(3ajg VHWs
(3cJHgG GdfGSN HQSe eMeO Hf YHOGdbGOQ GHf Cejf GdOhdIs
(3hGdfSNI ebGHdIs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs